Strategi Lazismu Pusat Dalam Meningkatkan Kepercayaan Muzakki - Moh Khoirul Anam; Siti Wardah; Bisri . (Journal of Islamic Economy and Business (JIsEB), 2024)
Zakat payers are less aware of the benefits of paying zakat through institutions. Zakat institutions receive less zakat funds than infaq funds. This shows that the collection of zakat funds is less than optimal. Based on the description of the research background, the aim of the research is to determine the efforts of the Amil Zakat Institution to increase confidence in paying zakat to existing institutions. And to find out what steps the Amil Zakat Institution will take to guarantee that the zakat given to the Amil Zakat Institution will be safe and will be distributed properly. This research was carried out using qualitative methods. From the other side and simply it can be said that the aim of qualitative research is to find answers to a phenomenon or question through the systematic application of scientific procedures using a qualitative approach. The results of this research are in increasing the trust of muzakki. LAZISMU provides evidence of strong reports to muzakki such as financial reports for companies, individual reports, and to muzakki who, if they provide large amounts of funds, will make their own report, not combine it with other reports.